How to Be a Perfect Stranger - Matlins, Stuart M.; Magida, Arthur J. (SkyLight Paths Publishing, 2006)
We North Americans live in a remarkably diverse society, and it’s increasingly common to be invited to a wedding, funeral, or other religious service of a friend, relative, or coworker whose faith is different from our own.